Health Extension on Prevention of Anemia for Female Cadres in Krendang Village, West Jakarta - Alvina, Alvina; Pusparini, Pusparini; Merijanti, Lie Tanu (Universitas Malahayati Lampung, 2025)
ABSTRACT Anemia is one of the conditions that may result in decreased work productivity and low academic achievement, because a person with anemia becomes weak, exhausted, fatigued, and limp, all of which may disturb the person’s concentration in working and learning. There are several factors that can cause anemia, one of which is poor knowledge about the prevention of anemia. Female cadres are expected to assist the government in disseminating the knowledge required in the prevention of anemia. The purpose of this Community Service (Pengabdian Kepada Masyarakat, PKM) is to provide education through health extension on the prevention of anemia to the female cadres of Krendang village (kelurahan), West Jakarta. During the Community Service tests are given before and after the health extension to determine the understanding of the participants about the presented matter. The test results showed an increased understanding after the health extension. Education through health extension was able to increase the understanding and knowledge of the female cadres. Further education of the female cadres is needed such that they become able to disseminate the prevention of anemia to the community. Keywords: Knowledge, Anemia, Female Cadres